Treatment outcome with a selective RET tyrosine kinase inhibitor selpercatinib in children with multiple endocrine neoplasia type 2 and advanced medullary thyroid carcinoma. (November 2021) - Shankar, Ananth; Kurzawinski, Tom; Ross, Emma; Stoneham, Sara; Beale, Tim; Proctor, Ian; Hulse, Tony; Simpson, Kate; Gaze, Mark N.; Cattaneo, Elene; Gevers, Evelien; Marshall, Lynley; et al.
Abstract: Background: Medullary thyroid carcinoma (MTC) in the context of multiple endocrine neoplasia type 2 (MEN2) is caused by mutations in the RET proto-oncogene. Therefore, in children with MEN2 and advanced MTC, the RET tyrosine kinase (TK) pathway is a target for treatment with selpercatinib, a selective RET TK inhibitor. Patients and methods: A retrospective review of the clinical, genetic, biochemical (calcitonin and carcinoembryonic antigen [CEA]) and imaging data of six medically untreated children with MEN2 and recurrent and or progressive MTC. The main parameters were safety and objective treatment response to selpercatinib. Results: Six children (three males and three females, aged 3–12 years), four with MEN2B and two MEN2A, are reported. All had initial total thyroidectomy and extensive neck dissections but subsequently developed recurrent and progressive disease. All experienced an improvement in clinical symptoms with a concomitant biochemical response evidenced by significant fall in serum calcitonin and CEA concentrations. The fall in serum calcitonin was evident within 2 weeks of the start of selpercatinib, and responses were ongoing at a median follow-up of 13 months (range, 11–22 months). Four children with measurable radiological disease had good volume reduction. The most common adverse effects were transient but reversible grade 1 or 2 increase in alanine aminotransferase, serum bilirubin and constipation. No child required a dose modification or had to discontinue selpercatinib because of a drug-related adverse event. Conclusion: Selpercatinib has shown excellent therapeutic efficacy with minimal toxicity in children with MEN2 and progressive metastatic RET -mutated MTC. Highlights: Children with MEN2-associated medullary thyroid carcinoma (MTC) are diagnosed late. Extensive surgery alone is ineffective in patients with advanced-stage MTC. Treatment with selpercatinib is effective without significant adverse effects.